Phacoemulsification in vitrectomized eyes: Maintaining the stability of the anterior chamber via a new technique. Issue 3 (May 2021) - Li, Xinxin; Li, Qiumei; Bano, Shazia; Li, Shaowei
Fluctuating anterior chamber depth and reverse pupillary block are the most common problems encountered during phacoemulsification following pars plana vitrectomy in cases of cataracts. The sudden deepening of the anterior chamber makes the surgical procedure more cumbersome and increases the risk of intraoperative complications. To solve this problem, we describe a method of balancing the pressure of the anterior and posterior chamber by using a syringe with a flushing needle to inject balanced salt solution into the posterior chamber via the gap between the iris and the anterior capsule of the lens. This technique is especially suitable for complicated cataracts following previous pars plana vitrectomy and high myopia-complicated cataracts. This technique yielded promising results in reducing the difficulties that occur during surgical procedures, reduced the risk of intraoperative complications and simplified the intraocular lens implantation.